Chemoradiation-Altered Micromilieu of Glioblastoma Cells Particularly Impacts M1-like Macrophage Activation - Shojaei, Mona; Frey, Benjamin; Putz, Florian; Fietkau, Rainer; Gaipl, Udo; Derer, Anja (International Journal of Molecular Sciences, 2025)
Glioblastoma is a highly aggressive brain tumor with an overall poor prognosis due to its immunosuppressive tumor microenvironment (TME). Microglia and tumor-associated macrophages (TAMs) with pro-tumorigenic properties are dominant populations of immune cells in the glioblastoma TME. To date, several studies targeting TAMs to fight tumor progression in different tumor entities have been initiated. However, the impact of standard therapy schemes of glioblastoma cells on macrophage polarization, activation, and phagocytosis remains controversial. The same applies to the relevance of PD-1/PD-L1 blockade in the interaction between macrophages and tumor cells. Our study, therefore, investigated patient-oriented treatment of GLIOBLASTOMA by examining the phagocytic capacity of polarized M1- and M2-like macrophages using GL261-luc2 tumor cells as a preclinical model system. Additionally, we analyzed the expression of activation and immune checkpoint markers on these macrophage subtypes following contact with tumor cells and their microenvironment. These factors were also determined after PD-1 blockade was initiated. The analyses revealed that the immunoregulatory M2-like macrophages generally exhibited a higher phagocytosis rate than the pro-inflammatory M1-like macrophages; however, this was not influenced by the pretreatment of glioblastoma cells with chemo- or radiotherapy. This could not be improved by blocking the PD-1 receptor. Furthermore, there were no modulations in the expression of differentiation, activation, or immune checkpoint molecules of M1- and M2-like macrophages after cell-to-cell contact with glioblastoma cells. But the medium conditioned by tumor cells strongly altered M1-like macrophages toward a more activated state, whereas M2-like cells were only mildly influenced. This was further enhanced by tumor cell treatment, with the most prominent effect after irradiation. These results suggest that conventional GLIOBLASTOMA tumor cell treatment affects the immunogenic status of macrophage subtypes, which is relevant for enhancing the anti-tumor immune response in brain tumors.
CRIS-Team Scopus Importer:2025-08-08
Keywords: chemoradiation; glioblastoma; immune checkpoint molecule; macrophages; PD-1; PD-L1/L2; TAM